“Living Images” Versus “Secularization”: Alternative Interpretations of Japanese Sculpture of the Kamakura Period - Vaneian, Elizaveta S. (Actual Problems of Theory and History of Art, 2022)
In this article, I revise some ideas that were developed by Soviet and Russian scholars in regard to sculpture of the Kamakura period (1185–1333). N. A. Vinogradova and Y. A. Kuzhel’ use in their writings such notions as “proximity to common people” and “secularization” when describing the style of this sculpture. However, from this perspective it is impossible to make sense of such common customs of the period as putting dedication materials inside the sculpture or the creation of “naked” statues. Exploring the source of such interpretation, I suggest that it derives from the circumstances of the Soviet times preventing scholars from investigating too closely the religious context of the art. On the other hand, I make a point that the dialogue or opposition of the religious (abstract) and naturalistic (secular) is a common place of the art historical discourse, probably deriving from the Vienna school of art history. I suggest revising this interpretation of Kamakura sculpture according to the latest scholarship of Buddhist imagery. In this scholarship, we can frequently see the notion of the “living images”, meaning that Buddhist cult images can be regarded as living entities not only on popular level, but also in writings of Buddhist teachers on the subject. With references to religious studies written in Russian and English, I introduce theories and ideas of Japanese Buddhist teachers relevant to the understanding of sculpture of the Kamakura period. As it turns out, the word “living” is particularly relevant to the Kamakura statues as it is precisely during these times that the cult of statues as living Buddhas (shōjin butsu) has spread. According to Japanese scholars, this cult can be the very reason of the naturalistic rendering of the statues and the way the inner space was adorned. Thus, we can hardly speak about the “secularization” of Kamakura sculpture.